Dampak Penurunan Tarif Impor Komoditas Pertanian pada Kesejahteraan (Analisis Keseimbangan Parsial, 2015) - Iin Inayah (Universitas Diponegoro, 2020)
Trade liberalization in agricultural sector for developing countries is a formidable challenge, because competition for agricultural product competitiveness is getting tougher. Commitment to WTO and role of IMF pushed Indonesia to apply agricultural import tariffs from 0 to 5 percent for all commodities, except rice and sugar in period 1998 to 2004. However, import tariff policies have increased after 2004. This study aims to measure impact of decreasing import tariffs on agricultural commodities on welfare. The method used is a partial equilibrium analysis, which analyzes a policy impact in a small scope by ignoring the impact on other sectors. The data used are aggregate import price, exchange rates, aggregate wholesale prices, aggregate consumer prices, aggregate production, aggregate consumption, and aggregate net imports in 2015. The impact of tariff changes is measured in five scenarios with an initial tariff of 25%, namely tariff reduction by 5%, then consecutive tariffs reduction of 10%, 15%, 20% and 24%. The results of study shows that the impact of the tariff reduction in Scenario 1 increases the net surplus by IDR 79,621.73 billion, next consecutive scenario contributes IDR 213,199.73 billion, IDR 344,581.05 billion, IDR 473,765.69 billion, and IDR 575,531.80 billion. In general, tariffs reduction effect to increasing net surplus, which means increasing the welfare on agricultural sector. However, tariffs reduction that should be done is 10% as in Scenario 2 because it gives the smallest impact on producers (farmers) and the government, but the benefits to consumers (societies) remain same.